Noninterventional Observational Study Using High‐Dose Controlled‐Release Oxycodone (CR Oxycodone) for Cancer Pain Management in Outpatient Clinics. Issue 12 (6th September 2013) - Baek, Sun Kyung; Shin, Hye Won; Choi, Young Jin; Zang, Dae Young; Cho, Do‐Yeun; Ryoo, Hun Mo; Baek, Jin Ho; Kim, Sam Yong; Song, Hong‐Suk
Abstract Purpose Efficacy, safety, and quality of life (QoL) for patients receiving larger doses of controlled‐release oxycodone (CR oxycodone) in outpatient clinics are evaluated. Methods The use of high‐dose CR oxycodone and adjuvant drugs for pain management, pain intensity, parameters associated with quality of life, and adverse effects in cancer patients treated with high‐dose CR oxycodone (≥80 mg/day) was prospectively observed for 8 weeks. Data from 486 cancer patients receiving high‐dose CR oxycodone were collected from 44 hospitals during the period from February 2009 to March 2010. Results Three hundred eighteen of the total 486 patients treated with high‐dose CR oxycodone were followed up for 8 weeks. Pain intensity significantly improved from a mean numeric rating scale (NRS) 5.49 to NRS 4.33 (P < 0.0001). Dosage of CR oxycodone increased from a mean of 130.0 to a mean of 174.9 (P < 0.0001). QoL including activity, walking, and sleeping significantly improved after 8 weeks. At baseline, 138 complained of adverse effects, of which constipation (30.2%) was the most common followed by dry mouth (8.8%) and dizziness (8.2%). After 8 weeks, 128 patients complained of adverse effects such as constipation (27.0%), nausea (5.7%), dry mouth (5.7%), and dizziness (5.0%). After 8 weeks of high‐dose CR oxycodone, adverse effects did not increase. Conclusion This study suggests that over an 8‐week period, the use of high‐dose CR oxycodone for cancer pain management is efficient, safe, and tolerable in outpatient clinics.